Advances in Databases and Information Systems 15th International Conference, ADBIS 2011, Vienna, Austria, September 20-23, 2011. Proceedings - Eder, Johann; Bielikova, Maria; Tjoa, A Min (Springer eBooks., 2011)
This book constitutes the refereed proceedings of the 15th International Conference on Advances in Databases and Information Systems, ADBIS 2011, held in Vienna, Austria, in September 2011. The 30 revised full papers presented together with 2 full length invited talks were carefully reviewed and selected from 105 submissions. They are organized in topical sections on query processing; data warehousing; DB systems; spatial data; information systems; physical DB design; evolution, integrity, security; and data semantics.